Hak Asasi Manusia Menurut Undang-Undang Nomor 9 Tahun 1991 - Maftuhi, Ekrom (SALAM: Jurnal Sosial dan Budaya Syar-i, 2016)
Human Rights are natural rights that must be respected by everyone.Human rights are given from God. Nevertheless, fulfilling the human rights need statepolicy to commit and to implement human rights. Moreover, if the state declarerechstaat, the state must fullfill and respect the human rights as the requirement ofRechstaat. In Indonesia, the development and the history of fullfilling and respectingthe human rights happened in such important periode. Means, to respect and to fulfillthe human rights depend on the state policy even the human rights given from God.Â DOI: 10.15408/sjsbs.v3i3.7860